The Relationship of Workplace Conflict Management and Employee Satisfaction - K MANIENDARAN, SANJEEVAN (Research in Management of Technology and Business, 2023)
In the fast-moving corporate world, employee satisfaction has become the key of the success for each company. Conflict is inevitable in all living organisms; it is a natural phenomenon and social occur among humans wherever and when they are. There is evidence of existence of conflict since the beginning of the creation of what happened between Adam’s Son Cain and Abel, and ended up killing someone. Therefore, the purpose of the study is to identify the relationship of workplace conflict management and the employee satisfaction of company X. In addition, this study was carried out referring to pass studies and also by interviewing all level of contacts on the organization both the management and also the staff. Besides, also by reviewing their in used policies relating to workplace conflict management. The study found that there is a relationship between workplace conflict management and employee satisfaction. Apart from that, the results proved that workplace conflict management influenced employee satisfaction.  This study is important to extend the understanding of workplace conflict management towards the effects of it on higher management, supervisors and employee satisfaction by using research design and data collection method.